(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article focuses on the study of the relations of liberalization of the Egyptian economy and the reconstruction of foreign policy relations, the main argument of which is the restructuring of Egyptian foreign policy. In the process, various forms of interaction of the Egyptian economy and foreign policy are studied.